2016
DOI: 10.1007/s00280-016-3169-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polydopamine as a new and biocompatible coating of magnetic nanoparticles for delivery of doxorubicin in mouse breast adenocarcinoma

Abstract: Magnetic DOX-IP demonstrates effective tumor-targeted drug delivery in a mouse model of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…However, the employment of MMIPs as carriers of anticancer agents is emerging. Only a few publications reported the development of MMIPs with the aim of smart delivery of anticancer drugs local to the tumor [ 3 , 50 , 54 , 61 , 65 , 68 , 77 , 78 , 79 , 80 , 81 ] that shed light on the development of a novel generation of multifunctional hybrid DDSs and future perspectives in this field.…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the employment of MMIPs as carriers of anticancer agents is emerging. Only a few publications reported the development of MMIPs with the aim of smart delivery of anticancer drugs local to the tumor [ 3 , 50 , 54 , 61 , 65 , 68 , 77 , 78 , 79 , 80 , 81 ] that shed light on the development of a novel generation of multifunctional hybrid DDSs and future perspectives in this field.…”
Section: State Of the Artmentioning
confidence: 99%
“…5-FU, DOX and EPI with a broad antineoplastic spectrum are used to treat many different types of cancer as colon or rectum, breast, liver, bladder and brain [ 50 , 61 , 79 , 80 ]. The main drawbacks of direct chemotherapy with these agents can be listed as severe depression of hematopoiesis (anemia, leucopenia, thrombopenia), infection and cardiotoxicity regarding EPI [ 50 ], 5-FU resistance and rapid clearance from the body [ 6 ] and DOX cumulative cardiotoxicity and nephrotoxicity [ 82 ].…”
Section: State Of the Artmentioning
confidence: 99%
“…DOX [93,103] and 5-FU [64] PDA-based imprinted polymers were used to coat magnetic and silica NPs. The imprinted polymers showed a fast release of DOX and 5-FU, as 80% of template drug was released from the NPs within 4 h, with a maximum release after 24 h [64,93,103]. One important advantage of MIP-based PDA preparation is however, the use of mild alkaline aqueous media, which allows the synthesis of water-compatible MIPs.…”
Section: Biocompatibility and Biodegradability Of Mip-ddsmentioning
confidence: 99%
“…Magnetic NPs are frequently used for DDS development intended for cancer treatment, because they can be easily tracked, manipulated, and directed towards tumor site using external magnetic field. Iron oxide NPs are the only approved types of magnetic NPs for biomedical applications [107], magnetite being one of the naturally occurring iron oxides in human heart, liver, and spleen [103]. However, for in vivo applications their surface needs to be coated with biocompatible materials, since it was shown that they can induce severe toxicity via protein denaturation [108].…”
Section: Biocompatibility and Biodegradability Of Mip-ddsmentioning
confidence: 99%
See 1 more Smart Citation